2019
DOI: 10.1002/art.40810
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Gene Expression Biomarkers as a Classifier of Methotrexate Nonresponse in Patients With Rheumatoid Arthritis

Abstract: Objective. Approximately 30-40% of rheumatoid arthritis (RA) patients who are initially started on low-dose methotrexate (MTX) will not benefit from the treatment. To date, no reliable biomarkers of MTX inefficacy in RA have been identified. The aim of this study was to analyze whole blood samples from RA patients at 2 time points (pretreatment and 4 weeks following initiation of MTX), to identify gene expression biomarkers of the MTX response.Methods. RA patients who were about to commence treatment with MTX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 29 publications
1
37
2
Order By: Relevance
“…Comparing the background at the start of ABA treatment, the percentage of MTX users was different in responders and non-responders. Recently, it has been reported that the expression level of the type 1 IFN is higher in patients that do not respond to methotrexate [42]. As there was no difference in the type I IFN scores among MTX users and non-users in both responders and non-responders in this study (data not shown), the cause of the difference in type I IFN expressions between the responders and the non-responders is not attributed to the percentage of MTX use.…”
Section: Discussionmentioning
confidence: 38%
“…Comparing the background at the start of ABA treatment, the percentage of MTX users was different in responders and non-responders. Recently, it has been reported that the expression level of the type 1 IFN is higher in patients that do not respond to methotrexate [42]. As there was no difference in the type I IFN scores among MTX users and non-users in both responders and non-responders in this study (data not shown), the cause of the difference in type I IFN expressions between the responders and the non-responders is not attributed to the percentage of MTX use.…”
Section: Discussionmentioning
confidence: 38%
“…However, gene expression profiles from whole blood RNA showed an overrepresentation of type I interferon pathway genes in nonresponders. This signature explained 78% of the AUC, a significant improvement over clinical assessment 19 . Recently, combining clinical and genomic variables (specifically, genotypes of adenosine triphosphatebinding cassette transporter implicated in active MTX efflux from cells) yielded a model with an AUC of 80% 20 , illustrating how various sources of biomarkers can synergize productively.…”
Section: Next-generation Computational Biomarkersmentioning
confidence: 91%
“…Next-generation Biomarkers: HOPE and HYPE • Response to treatment Today, predicting response to MTX (methotrexate) remains impossible. Clinical covariates such as age, smoking status, antibodies, joint counts, and patient evaluations only explained 63% of the area under the receiver operating characteristics (ROC) curve (AUC) to predict MTX nonresponse 19 . However, gene expression profiles from whole blood RNA showed an overrepresentation of type I interferon pathway genes in nonresponders.…”
Section: Next-generation Computational Biomarkersmentioning
confidence: 99%
“…In rheumatoid arthritis gene signature has been shown to assist response prediction. 77 In the current treatment of lupus longterm clinical and immunological remission is only achieved in a proportion of patients. The inherent pathophysiological complexity of lupus described at the cellular and molecular level cannot be overstated.…”
Section: Current Treatment Of Lupusmentioning
confidence: 99%